The structure of the X-ray absorber in Mrk 915 revealed by Swift. Issue 4 (9th September 2015) - Severgnini, P.; Ballo, L.; Braito, V.; Caccianiga, A.; Campana, S.; Della Ceca, R.; Moretti, A.; Vignali, C.
Abstract: In this paper, we present the results obtained with a monitoring programme (23 days long) performed with Swift -XRT on the local Seyfert galaxy Mrk 915. The light-curve analysis shows a significant count rate variation (about a factor of 2–3) on a time-scale of a few days, while the X-ray colours show a change in the spectral curvature below 2 keV and the presence of two main spectral states. From the spectral analysis we find that the observed variations can be explained by the change of the intrinsic nuclear power (about a factor of 1.5) coupled with a change of the properties of an ionized absorber. The quality of the data prevents us from firmly establishing if the spectral variation is due to a change in the ionization state and/or in the covering factor of the absorbing medium. The latter scenario would imply a clumpy structure of the ionized medium. By combining the information provided by the light curve and the spectral analyses, we can derive some constraints on the location of the absorber under the hypotheses of either homogeneous or clumpy medium. In both cases, we find that the absorber should be located inside the outer edge of an extended torus and, in particular, under the clumpy hypothesis, it should be located near, or just outside, to the broad emission line region.